1991
DOI: 10.1164/ajrccm/143.3.572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Capsaicin on Mechanical, Cellular, and Mediator Responses to Antigen in Sensitized Guinea Pigs

Abstract: To assess the role of tachykinins (TKs) in immediate hypersensitivity allergic reactions in guinea pigs (GPs), we compared airway mechanics and bronchoalveolar lavage (BAL) cell and inflammatory mediator profiles in three groups of GPs after ovalbumin aerosol challenge: (1) saline-sensitized, noncapsaicinized (control) (n = 9); (2) ovalbumin-sensitized, noncapsaicinized (OS) (n = 9); (3) ovalbumin-sensitized capsaicinized (OSC) (n = 9). Lung resistance (RL), dynamic elastance (EL), BAL cell counts, histamine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 4 publications
5
12
0
Order By: Relevance
“…Though not in every experimental condition (Ingenito et al, 1991), the involvement of capsaicin-sensitive fibres in models of allergy is well established (Saria et al, 1983;Manzini et al, 1987;Alving et al, 1987;Gentilini et al, 1990c;Kohrogi et al, 1991). This was also confirmed under our experimental conditions, where depletion of neuropeptide-containing terminals by superfusion with capsaicin reduced the tracheal strip response to OA.…”
Section: Discussionsupporting
confidence: 84%
“…Though not in every experimental condition (Ingenito et al, 1991), the involvement of capsaicin-sensitive fibres in models of allergy is well established (Saria et al, 1983;Manzini et al, 1987;Alving et al, 1987;Gentilini et al, 1990c;Kohrogi et al, 1991). This was also confirmed under our experimental conditions, where depletion of neuropeptide-containing terminals by superfusion with capsaicin reduced the tracheal strip response to OA.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, IBR was not significantly inhibited by capsaicin pretreatment in model I and model II animals, indicating that neurokinins were not highly involved in the ovalbumin-induced IBR. These results are consistent with the previous observations that capsaicin pretreatment did not prevent the allergen-induced immediate bronchoconstriction in guinea pigs [32, 33], and that intravenous administration of neurokinin receptor antagonist had no effects on the immediate ovalbumin-induced bronchoconstriction [34]. On the other hand, other reports have shown that capsaicin pretreatment inhibited respiratory system resistance and elastance after antigen inhalation in guinea pigs repeatedly sensitized with ovalbumin aerosol [20], and capsaicin pretreatment resulted in a decreased immediate pulmonary mechanical response to antigen inhalation in sensitized guinea pigs [19].…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, capsaicin pretreatment had no effect on eosinophil accumulation in model I animals. This is consistent with the previous observation in which capsaicin pretreatment did not affect increase in BALF cell counts after antigen inhalation in sensitized guinea pigs [32]. We have previously observed that ovalbumin-induced eosinophil accumulation is inhibited by thromboxane synthase inhibitor and platelet-activating factor antagonist in a guinea pig model of mild asthma [46].…”
Section: Discussionsupporting
confidence: 93%
“…Although Ingenito et al (1991) andLai, (1991) suggested that tachykinins do not contribute to the bronchoconstriction evoked by antigen challenge in sensitized guinea-pigs, found that tachykinins released from sensory nerves play a significant role in antigen-induced bronchoconstriction. The latter group investigated the bronchoconstrictor effect of inhaled ovalbumin (OA) at low and high concentrations after pretreatment with phosphoramidon, NKI and NK2 receptor antagonists in sensitized guinea-pigs in vivo.…”
Section: Discussionmentioning
confidence: 99%